1986
DOI: 10.1128/jcm.23.1.197-198.1986
|View full text |Cite
|
Sign up to set email alerts
|

Method for the typing of Clostridium difficile based on polyacrylamide gel electrophoresis of [35S]methionine-labeled proteins

Abstract: A typing method for Clostridium difficile based on the incorporation of [35S]methionine into cellular proteins, their separation by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, and their visualization by autoradiography is described. On analysis of the radiolabeled-protein profiles, nine distinct groups were observed (A to E and W to Z). The method, which is simple, reproducible, and readily expandable, has been applied in epidemiological studies to demonstrate cross-infection and hospital acquis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…These remarkable features were also found in the composition of antigen S of C. botulinum type A 190L (31). The molecular weight of the 32K antigen determined by sedimentation equilibrium (30,200) was fairly consistent with that estimated by SDS-PAGE (32,000), suggesting that the antigen molecule is a single polypeptide chain. The molecular weight of the 32K antigen is lower compared with the other RA proteins with molecular weights from about 41,000 to 200,000 (13,29).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…These remarkable features were also found in the composition of antigen S of C. botulinum type A 190L (31). The molecular weight of the 32K antigen determined by sedimentation equilibrium (30,200) was fairly consistent with that estimated by SDS-PAGE (32,000), suggesting that the antigen molecule is a single polypeptide chain. The molecular weight of the 32K antigen is lower compared with the other RA proteins with molecular weights from about 41,000 to 200,000 (13,29).…”
Section: Discussionsupporting
confidence: 64%
“…Epidemiological studies have demonstrated that clustering of the cases and outbreaks of the colitis are due to the nosocomial spread of this organism (7,16,25). To date, various typing methods of C. difficile strains have been reported: Nakamura et al (20) classified them into four serovars by the crossed agglutination test using formol-treated cells; Delmee et al (6) defined six serogroups based on the slide agglutination; and Tabaqchali et al (30) grouped them into nine serovars by employing the electrophoresis of labeled cellular protein. However, immunochemical and physicochemical properties of the cellular components, which are responsible for these serological reactions, have not yet been thoroughly elucidated.…”
mentioning
confidence: 99%
“…Typing by PAGE overcomes such problems especially as the same approach can be used for other organisms (which for serotyping would each require a large range of sera). Other organisms to which PAGE typing has been applied include Acinetobacter (Alexander et al 1984), Bacteroides (Taylor et al 1987), Campylobacter (Costas et al 1987b), Clostridium (Tabaqchali et al 1986) and Streptobacillus .…”
Section: Discussionmentioning
confidence: 99%
“…Nine standard strains of C. dlfficile, designated A-E and W-Z, were used [5,6] . The identity of the clostridal strains was confirmed by smell, colony morphology and gas-liquid chromatographic analysis of volatile fatty acids [7].…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…Three types of antigen were prepared for rabbit immunisations: i) C difficile whole cells from the 9 standard typed strains (A E and W-Z, identified by 35S-methionine labelled protein profiles [6]), were prepared from formalised cell antigens as described previously [5]. ii) E. coli lysates containing cloned C. difficile antigens were prepared from a confluent lawn of plaques on 10 plates (90 mm diameter) overlaid with 0.5 ml SM buffer (0.1 M NaC1, 10 mM MgSO4, 50 mM Tris (ph 7.5), 0.01% gelatine) for 1 h at 25 ° C. The plate lysate suspension was centrifuged (Hi-Spin 21 MSE Scientific Instruments, U.K.) at 7000 × g for 15 rain and the supernatant was used for rabbit immunisation.…”
Section: Rabbit Antiserum Preparationmentioning
confidence: 99%